Contract Risks and Credit Spread Determinants in the International Project Bond Market - Dailami, Mansoor (World Bank, Washington, DC, 2014)
International bond markets have become an increasingly important source of long-term capital for infrastructure projects in emerging market economies over the past decade. The Ras Laffan Liquified Natural Gas (Ras Gas) project represents a milestone in this respect: its $1.2 billion bond offering, completed in December 1996, has been the largest for any international project. The Ras Gas project has the right to extract, process, and sell liquefied natural gas (LNG) from a field off the shore of Qatar. The principal off-taker is the Korea Gas Corporation (Kogas), which resells most of the LNG to the Korea Electric Power Corporation (Kepco) for electricity generation. In this clinical study the authors analyze the determinants of credit spreads for the Ras Gas project in terms of its contractual structure, with a view to better understanding the role of contract design in facilitating access to the global project bond market. Market risk perceptions have long been recognized to be a function of firm-specific variables, particularly asset value as embodied in contracts. The authors therefore study the impact of three interlocking contracts on the credit spreads of the project's actively traded global bonds: the 25-year output sales and purchase agreement with Kogas-Kepco, the international bond covenant, and an output price-contingent debt service guarantee by Mobil to debt holders. Using a sample of daily data from January 1997 to March 2000, the authors find that the quality of the off-taker's credit-and, more important, the market's assessment of the off-taker's economic prospects-drive project bond credit spreads and pricing. In addition, seemingly unrelated events in emerging debt markets spill over to project bond markets and affect risk perceptions and prices in this segment. Judicious use of an output price-contingent debt service guarantee by shareholders can significantly reduce project risks, and markets reward issuers through tighter credit spreads. Bondholders and shareholders share residual risks over time, despite covenants meant to preempt risk shifting. This type of risk shifting originates from incomplete contracts and the nonrecourse nature of project finance. It does not necessarily result from a deliberate attempt by management to increase shareholder value at the expense of debt holders by pursuing high-risk, low-value activities, although project managers and shareholders could still exploit their informational advantages by leaving output supply contracts incomplete in ways beneficial to their private interests. The results hold important lessons for global project finance. Projects incorporating certain design features can reap significant financial gains through lower borrowing costs and longer debt maturities: Judicious guarantees by parents that enjoy a particular hedging advantage enhance a project's appeal, as reflected in favorable pricing. Pledging receivables rather than physical assets as collateral and administering investor cash flows through an off-shore account offers additional security to debt holders. Projects should use their liability structure to create an implicit option on future private debt financing that matches the real option of a project expansion. The finding that bondholders bear residual risks means that shareholders can reduce their risks arising from bilateral monopolies and buy insurance against unforeseen and unforeseeable events.